Comparing the IMF and the ESM through Bond Market Premia in the Eurozone - Kiss, Gábor Dávid; Csiki, Máté; Varga, János Zoltán (Public Finance Quarterly, 2023)
In many European Union (EU) member countries, the financial turmoil that started in 2008 resulted in a banking and/or sovereign debt crisis. The EU did not have dedicated tools to handle the situation and it became clear that neither the IMF loans, nor the ad hoc intergovernmental loans provided satisfactory solutions. This motivated the establishment of the European Stability Mechanism (ESM). In this study, we compared the lending activity of the IMF and the ESM, their institutional background, and using panel regression methods we investigated the effect of EFSM-ESM loans on monthly sovereign bond yield premia. Results: The ESM programmes worked against bond market divergence, yield premia decreased, and they moved more closely together – which is a precondition of an efficient eurozone-wide monetary policy. Since EFSM-ESM bonds are guaranteed by euro area member states, it fulfils the solidarity principle of the optimum currency area, and with the help of EFSM-ESM programmes, sovereign defaults have been successfully avoided.